PENERIMAAN DIRI ORANG TUA YANG MEMILIKI ANAK BERKEBUTUHAN KHUSUS DI KECAMATAN SIMEULUE TIMUR KABUPATEN SIMEULUE - Nurul Rahmi; Arifin Zain; Rofika Duri (UIN Sumatera Utara, 2026)
This study aims to describe the process of self-acceptance among parents of children with special needs (ABK) in Kuala Makmur Village, East Simeulue District. The method used is a descriptive qualitative approach. Data was obtained through observation, interviews with five parents, and documentation. The results of the study indicate that initially, parents experienced emotional reactions such as sadness, shock, disappointment, and guilt when learning about their child’s condition. Over time, they began to accept their child’s condition through family support, especially from their spouse, religious values, knowledge about ABK, and support from the social environment. The process of self-acceptance resulted in changes in parenting patterns to be more patient, attentive, not comparing children, and more focused on developing children’s independence. Despite challenges such as social stigma and limited information, parents remained optimistic about their children’s future. The conclusion of this study confirms that self-acceptance is influenced by internal and external factors that are interrelated in shaping positive parenting patterns.Keywords: Self-Acceptance, Parents, Children with Special Needs